PENTINGNYA PENINGKATAN SUMBERDAYA MANUSIA DALAM PENYELENGGARAAN ADMINISTRASI PERKANTORAN PADA KANTOR SEKRETARIAT DAERAH KABUPATEN KEPULAUAN SANGIHE - Mambo, Rully (Sam Ratulangi University, 2015)
The management of office administration on the wide organization and the big scale like regionalsecretariat office, in fact not an easy job. Therefore more needed sufficient capability from office manageror executing. The purposes of this research to know The Increasing Importance of Human Resources onThe Regional Secretariat Office Sangihe Archipelago Regency.Data analysis techniques on this research is descriptive qualitative analysis is analysis conducted for,describe, observe, delineate, embrace even summarize observation result has been done in the field.Population on research is government employees in the Regional Secretariat Office Sangihe Regency asmany as 178 peoples.The result of research to show human resources more important on the management of officeadministration, in this case the quality of the staff or employee. The inadequacy of human resources inthe Regional Secretariat Office Sangihe Regency evidently very important role to employee on themanagement of office administration.Keywords : Human Resources, Office Administration